2004
DOI: 10.1177/0733464804263129
|View full text |Cite
|
Sign up to set email alerts
|

Driving Cessation and Health in Older Women

Abstract: To study the association of health and driving cessation in older female drivers, a mail survey was sent to all Finnish women born in 1927 who gave up their driver license at the age of 70 (n = 1,476) and to a corresponding random sample of women who renewed their license at the age of 70 (n = 1,494). The ex-drivers had poorer overall health status than the drivers, but the health conditions related to driving cessation were in general not of the type impairing driving ability but rather decreasing overall wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(69 citation statements)
references
References 21 publications
3
66
0
Order By: Relevance
“…Results suggest that older drivers should not be tested on the basis of their age but on the basis of their observed or reported abilities because the goal is to preserve mobility while ensuring public safety (Staplin & Lococo, 2003;Molnar, Eby, & Dobbs, 2005). In addition, some research has shown that age-based screening policies cause certain subgroups of safe, capable drivers (especially women) to stop driving prematurely (Siren, Hakamies-Blomqvist, & Lindeman, 2004). More recent work proposes that driver diagnostics and screenings can improve safety and be cost-effective if they target subgroups of drivers who have identifiable high-risk factors, such as diagnosed dementia, rather than targeting the general population (Hakamies-Blomqvist, Siren, & Davidse, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Results suggest that older drivers should not be tested on the basis of their age but on the basis of their observed or reported abilities because the goal is to preserve mobility while ensuring public safety (Staplin & Lococo, 2003;Molnar, Eby, & Dobbs, 2005). In addition, some research has shown that age-based screening policies cause certain subgroups of safe, capable drivers (especially women) to stop driving prematurely (Siren, Hakamies-Blomqvist, & Lindeman, 2004). More recent work proposes that driver diagnostics and screenings can improve safety and be cost-effective if they target subgroups of drivers who have identifiable high-risk factors, such as diagnosed dementia, rather than targeting the general population (Hakamies-Blomqvist, Siren, & Davidse, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Older women are also more likely to give up driving prematurely; that is, when they are still fit to drive (e.g., Bauer, Adler, Kuskowski, & Rottunda, 2003;Hjorthol, 2013;Siren, Hakamies-Blomqvist, & Lindeman, 2004;Siren & Haustein, 2014b;Transek, 2005).…”
Section: Gendermentioning
confidence: 99%
“…Women especially often give up their licence when they are still fit to drive (Siren and Haustein, 2014;Siren et al 2004) and could be even more encouraged to do so by an extensive renewal procedure. If the population based health visits at certain ages are seen as a necessary societal investment, we recommend these visits to have more meaningful scope than that of traffic safety only.…”
Section: Discussionmentioning
confidence: 99%
“…First, screening aims to assess "individual risk", which has been criticised conceptually (Hakamies-Blomqvist, 2006 Siren et al 2004). Their mobility thereafter is likely to be maintained through less safe modes of transportation.…”
Section: Methodological Aspectsmentioning
confidence: 99%
See 1 more Smart Citation